BMI is superior to symptoms in predicting response to proton pump inhibitor: randomised trial in patients with upper gastrointestinal symptoms and normal endoscopy. Issue 4 (15th December 2010) - Fletcher, Jonathan; Derakhshan, Mohammad H; Jones, Gareth-Rhys; Wirz, Angela A; McColl, Kenneth E L
Abstract : Objectives: In most patients undergoing endoscopy for upper gastrointestinal (GI) symptoms in the Western world, no macroscopic abnormality or evidence of Helicobacter pylori infection is identified. Following this negative investigation, proton pump inhibitor (PPI) therapy is usually prescribed. The aim of this study was to assess the value of such treatment compared with placebo and to identify predictors of response. Design: Prospective parallel randomised study. Setting: Dyspepsia Research Clinic. Participant: 105 patients (49 men, median age 44 years, IQR 22) with normal endoscopy and H pylori negative with ongoing upper GI symptoms following 2-week run-in period. Intervention: Full demographic symptom severity and characteristics were assessed and 24 h oesophageal pH metry and oesophageal manometry were performed prior to randomisation to 2 weeks of treatment with lansoprazole 30 mg/day or placebo (2:1), with reassessment of symptom severity during the second week of treatment. Primary outcome: 50% reduction in Glasgow Dyspepsia Severity Score (GDSS). Results: According to intention to treat analysis, the response was 35.7% for the active group and 5.7% for the placebo group (p<0001). The only non-invasive independent predictor of response to PPI in multivariable analysis was the patient's body mass index (BMI) (p=0.003). The association of BMI with response to PPI was apparent across the full range of quartiles (p values for trend=0.01). BMI had a similar predictive value to either 24 h oesophageal pH metry or manometry. Predominant symptom and symptom subgroups were unhelpful in predicting the response to PPI. Including all pretreatment assessments, only BMI (p<0.05) and lower oesophageal sphincter pressure (p<0.05) were independent predictors of response. Conclusion: The response to PPI therapy is likely to be related to underlying acid reflux. The strong predictive value of BMI is probably due to its association with underlying reflux disease and the fact that it is a more objective and reproducible measure than symptom characteristics. It is recommended that BMI should be measured in patients with upper GI symptoms. Trial Registration Number: ISRCTN 32863375.